Exploring the implementation of online learning at medical-CLIL classes: EFL students’ satisfaction - Khoiriyah; Roy, Sukanto; Hasan, Md Kamrul (Journal of Education and e-Learning Research, 2025)
Due to the widespread implementation of online learning, it has become increasingly important for educators to identify key sources of online learning quality that influence students’ satisfaction levels. This research aimed to investigate student satisfaction and its influencing factors within the Indonesian EFL setting, specifically in Content and Language Integrated Learning (CLIL) classrooms. A purposive sample of 120 EFL students was selected from a private university in Indonesia. These students, majoring in medical sciences, participated in CLIL classes over two semesters during their first year, where English served as the vehicular language. A mixed-method approach was employed, utilizing questionnaires and interviews. The results indicated that EFL students generally reported a high level of satisfaction, with an overall mean score of 5.263, suggesting a very good satisfaction level. Importantly, the findings revealed no significant gender differences in student satisfaction. Several sources contributing to student satisfaction were identified, including the design of learning materials, flexibility, and helpfulness of lecturers. This study offers recommendations to enhance the effectiveness of online learning by analyzing the psychological features of EFL students across various research contexts, including similar settings.